The Role of Extracurricular, Intracurricular, and Co-curricular in Schools to Support Students’ Careers Based on Skilled Human Resources - Zulkarnaen, Moh. (Proceeding International Conference on Religion, Science and Education, 2025)
This research examines the role of extracurricular, intracurricular, and co-curricular activities in supporting students’ careers at school to create skilled human resources. Educational institutions are not only formal institutions that focus on learning but also help students’ careers. Looking at the current phenomenon, many students are confused about deciding their career, because there are still many students who only focus on the academic side but do not have interpersonal and communication skills as well as how to socialize in society. So apart from formal education, students must also be equipped with the development of life skills obtained through extracurricular, intracurricular, and co-curricular activities at school. The research method used is a literature review with a descriptive qualitative approach. Data sources were obtained from articles, books, previous research, social media, laws, and other sources. With extracurricular, intracurricular, and co-curricular activities, students can get many benefits, including developing life skills, exploring their potential talents, and interests, and having the ability to manage time, cooperation, and independence so that with these activities educational goals can be achieved. Apart from that, extracurricular, extracurricular, and co-curricular activities can support student achievement so that they become skilled human resources in the future.